STUDI FENOMENOLOGIS TERHADAP PERAN ETIKA DALAM PENDIDIKAN PERPAJAKAN - Widyaningrum, Tri Rahayu (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
Ethics, has a very important role in all aspects including the aspect of taxation Education. The existence of ethics is absolutely necessary within the framework of a healthy mindset and full balance so that the education process running for this not only focus on improving the capabilities, expertise and intellectual, but also pay attention to morality that comes to fruition ethics in the construction of education completely. This study aims to assess the understanding of the students in terms of knowledge about the role of ethics in education tax.The extent to which their understanding in terms of ethics and critical payloads contained in it. Phenomenology is used as an analytical tool understanding of the role of ethics in education tax. These findings indicate that students understanding the role of ethics that is so important in the educational process of taxation and will be used as stock ethics profession as a career offender taxes. significantly still needed effort for understanding the role of ethics in education taxation can achieve balance by integrating a variety of clever angles and interests as a whole.